Verbal Establishing Stimuli: Testing the Motivative Effect of Stimuli in a Derived Relation with Consequences. - Ju, Winifred C.; Hayes, Steven C. (Psychological Record)
The present study examined whether the presentation of stimuli in equivalence relations with consequences increases the operant behavior that produces these consequences. In Experiment 1, both normal words and experimentally trained equivalence stimuli did so with young children. In Experiment 2, results were similar with college students. Here, a computer-based task was used, pitting discriminative control established within the experiment against the possible motivative effect of stimuli in equivalence relations with consequences of known impact. Results suggest that such stimuli function as verbal establishing stimuli. Reprinted by permission of the publisher.